The historical imagination of sociology - Skocpol, Theda; Miskolci (Tradutor), Richard (FCL-UNESP Laboratório Editorial, 2007)
The text deals with the beginnings and the development of sociology historical tradition. It starts with an analysis of the partial eclipse of historical studies during the hegemony of functionalism and modernization theories, but its central subject is the re-emergence of the historical tradition in the works of nine scholars: Marc Bloch, Perry Anderson, E. P. Thompson, Barrington Moore, Karl Polanyi, Immanuel Wallerstein, Reinhard Bendix, Charles Tilly e S. N. Eisenstadt.